Hubungan Tingkat Pengetahuan Ibu dengan Tindakan Swamedikasi Diare Pada Anak di Desa Sidakarya Tahun 2024 - Jeliati Ludji; I Made Purnadhibrata; Maria Nathalia I. Istianti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Self-medication is the process of recognizing symptom complaints to obtaining medication and carrying out treatment independently. Diarrhea is a disease that causes feces to come out more than three times a day with a liquid consistency that can be accompanied by blood or mucus and the frequency is more frequent than normal. This research aims to determine the relationship between the level of maternal knowledge and self-medication for diarrhea in children in Sidakarya Village. The research method uses descriptive quantitative with a cross sectional study with accidental sampling technique. The number of respondents to this research was 35 people based on calculations using the Slovin formula. The research results showed that the level of self-medication knowledge for diarrhea was categorized as high at (91.4%) and self-medication for diarrhea was categorized as appropriate at (97.1%). Based on the chi-square test, the P-value was 0.001 and the calculated r value was 0.361, indicating that there was a relationship between the level of diarrhea self-medication knowledge and diarrhea self-medication actions.